Effects of scapular taping on the activity onset of scapular muscles and the scapular kinematics in volleyball players with rotator cuff tendinopathy - Leong, H. T.; Ng, G. Y.; Fu, S. N. (Journal of Science and Medicine in Sport, 2017)
Objectives To examine the effect of scapular taping on the activity onset of scapular muscles and the scapular kinematics during arm elevation in volleyball players with rotator cuff (RC) tendinopathy. Design Randomized placebo-controlled repeated measures Methods Twenty-six male volleyball players with RC tendinopathy (mean age = 23.6 ± 3.3 years) participated in the study. Electromyography (EMG) activity onset of upper trapezius (UT), middle trapezius (MT), lower trapezius (LT) and serratus anterior (SA) and the three-dimensional scapular kinematics quantified by using an acromial marker cluster method were compared with three scapular taping protocols, namely, no taping, therapeutic taping, and placebo taping. Results The MT, LT and SA activated significantly earlier in both therapeutic taping (all p < 0.005) and placebo taping conditions than no taping conditions (all p < 0.002). There was a small increase in the scapular upward rotation when therapeutic taping and no taping conditions were compared (p = 0.007). Conclusions Scapular taping may enhance the neuromotor control of the scapular muscles. Whether it provides adequate support for normal scapular kinematics during arm movement in athletes with RC tendinopathy await for further studies.